Strategi Rebalancing Amerika Serikat di Kawasan Asia-Pasifik - Planifolia, Vanilla (Jurnal Hubungan Internasional, 2017)
This paper will discuss why the United States changed its foreign policy from theÂ Middle East to Asia-Pacific region. The dynamic of the region shows that China plays an important role along with its national capability improvement. The increase in China's national capability is seen as a challenge to national interests, as well as security for the United States alliance states in the Asia-Pacific region. Using an analytical framework based on the Balance of Threat theory, the author concludes that there is a strong relation between China's national capability improvements with the implementation of US rebalancing strategy to the Asia-Pacific region.Tulisan ini mencoba menganalisa alasan Amerika Serikat mengubah fokus kebijakan luar negerinya dari Kawasan Timur Tengah ke Kawasan Asia-Pasifik. Dinamika kawasan yang terjadi, China memegang peran penting seiring dengan peningkatan kapabilitas nasionalnya. Peningkatan kapabilitas nasional China tersebut dilihat sebagai tantangan bagi kepentingan nasional, sekaligus keamanan bagi negara aliansi Amerika Serikat di Kawasan Asia-Pasifik. Dengan menggunakan kerangka analisa berdasarkan teori Balance of Threat, penulis menyimpulkan bahwa terdapat keterkaitan yang sangat kuat antara peningkatan kapabilitas nasional China dengan penerapan strategi rebalancing Amerika Serikat ke Kawasan Asia-Pasifik.